Peran Sistem Jaminan Produk Halal (SJPH) Dalam Menunjang Pertumbuhan Industri Halal Nasional - Dede San San Ramlan sandiyana; Wulan Safitri; Andinin Oktavia Widayanti; Lina Marlina (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
The implementation of the Halal Product Assurance System (SJPH) in Indonesia plays a vital role in ensuring product halalness while strengthening the competitiveness of the national halal industry. Through the appointment of Halal Supervisors and the preparation of the SJPH Manual, business actors are required to comply with halal standards established by the Halal Product Assurance Organizing Agency (BPJPH). The system functions not merely as a regulatory requirement but as a strategic instrument integrating Islamic principles throughout production, distribution, and marketing processes. Economically, the implementation of SJPH has a significant impact on empowering Micro, Small, and Medium Enterprises (MSMEs), expanding market access, and enhancing the competitiveness of Indonesian products in global markets. Government initiatives such as the Free Halal Certification Program (SEHATI) further accelerate inclusivity by enabling small businesses to participate in the halal ecosystem. With its gradual implementation and strong regulatory oversight, SJPH serves as a foundational mechanism for developing a sustainable, competitive, and trustworthy halal ecosystem, contributing greatly to Indonesia’s vision of becoming the world’s leading halal industry hub.